The Economic Implications of Maine’s Changing Age Structure - Breece, James; Mills, Glenn; Gabe, Todd (Maine Policy Review, 2015)
The authors analyze the major implications of Maine’s aging population on the state’s workforce and economy. They note that there are steps that can be taken to partially mitigate the negative impacts and capitalize on the opportunities associated with an aging population.
Keywords: aging; Maine; workforce; employment; population changes; household purchases; working-age-to-senior ratio